Laminated structure, electronic equipment and preparation method of laminated structure

By using a stacked structure of anti-fingerprint layer, anti-reflection layer, connecting layer and hardened layer in the folding screen mobile phone protection film, the bondable material is used to form chemical bonds, which solves the problem of poor wear resistance of the anti-reflection layer and improves the protective film Wear resistance and reliability.

CN119136605APending Publication Date: 2024-12-13HUAWEI TECH CO LTD +1

Patent Information

Application Number
CN202411093697.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The anti-reflective layer of the existing folding screen mobile phone protective film has poor wear resistance and is prone to scratches or fall off, resulting in poor user experience.

Method used

A laminated structure is adopted, including an anti-fingerprint layer, an anti-reflection layer, a connecting layer and a hardened layer. The connecting layer is made of bondable materials to form chemical bonds with the hardened layer, which enhances binding force and forms a thin layer of connecting layer on the hardened layer. To improve wear resistance.

Benefits of technology

It significantly improves the wear resistance and reliability of the stacked structure, reduces the risk of falling off of the anti-reflective layer, and improves the user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136605A_ABST
    Figure CN119136605A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a laminated structure, electronic equipment and a preparation method of the laminated structure, the laminated structure can be an optical laminated layer, and the laminated structure is arranged on the light emitting side of a display module, for example. The laminated structure comprises an anti-fingerprint layer, an antireflection layer, a first connecting layer, a hardened layer and a base film which are laminated from top to bottom, and the hardened layer is arranged on the upper surface of the base film. The first connecting layer is made of a bondable material, and the bondable material and the hardened layer form a chemical bond, so that a relatively strong bonding force is formed between the first connecting layer and the hardened layer, and the wear resistance of the laminated structure is improved. The thickness of the first connecting layer is relatively small, so that atoms with a higher proportion in the first connecting layer and the hardened layer are subjected to a cross-linking reaction to generate bonding, and the bonding force between the first connecting layer and the hardened layer can be further improved. And the surface of one side, deviating from the base film, of the hardened layer is smooth, and the wear resistance is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of display technology, and in particular to a laminated structure, an electronic device, and a method for preparing the laminated structure. Background Art

[0002] With the continuous development of display technology, foldable display terminals are gradually becoming a development trend of future mobile electronic products. When unfolded, foldable display terminals can obtain a larger display area to improve the viewing effect. When folded, foldable display terminals can obtain a smaller volume, which is convenient for users to carry.

[0003] At present, the protective film of foldable screen mobile phones includes a stacked base film, a hardening layer, an anti-reflection layer and an anti-fingerprint layer, among which the hardening layer has a higher hardness and better wear resistance. Among them, the anti-reflection layer can be prepared by a coating method (wet method), and the wear resistance is poor. The friction of the protective film during use by the user can easily cause the anti-reflection layer to be scratched or fall off, resulting in surface discoloration and poor user experience. Summary of the invention

[0004] The embodiments of the present application provide a laminated structure, an electronic device, and a method for preparing the laminated structure, which solve the problems of poor wear resistance and reliability of the protective film.

[0005] In order to achieve the above purpose, the embodiment of the present application adopts the following technical solution:

[0006] In the first aspect of the embodiment of the present application, a laminated structure is provided, which is arranged on a display module, and the laminated structure includes: an anti-fingerprint layer, an anti-reflection layer, a first connecting layer, a hardened layer and a base film arranged in a stacked manner; the hardened layer is arranged on the upper surface of the base film, the surface roughness of the hardened layer on the side away from the base film is 5-100nm, the thickness of the first connecting layer ranges from 1-20 atomic layers, the first connecting layer is made of a bondable material, and the bondable material forms a chemical bond with the hardened layer. Thus, the laminated structure connects the hardened layer and the anti-reflection layer through the first connecting layer, and the first connecting layer is made of a bondable material, so that a chemical bond is formed between the first connecting layer and the hardened layer, generating a strong bonding force, so that the film layer is not easy to fall off, and the wear resistance of the laminated structure is improved. And the first connecting layer is thin, and the wear resistance is better. And the surface roughness of the hardened layer is low, so that the surface of the anti-reflection layer prepared on the upper layer is also smooth, further improving the wear resistance of the anti-reflection layer.

[0007] In an optional implementation, the first connection layer includes silicon atoms, and the thickness of the first connection layer ranges from 1 to 5 silicon atomic layers. Thus, the thickness of the hardened layer is thinner, which can further enhance the atomic bonding force between the first connection layer and the hardened layer, and can further improve the wear resistance of the laminated structure.

[0008] In an optional implementation, the chemical bond formed between the hardened layer and the bondable material includes a covalent bond. Thus, a strong bonding force can be formed between the hardened layer and the first connecting layer, so that the film layer is not easy to fall off, and the wear resistance of the laminated structure is further enhanced.

[0009] In an optional implementation, the first connection layer is formed on the hardening layer by chemical vapor deposition or physical vapor deposition to form the chemical bond. Thus, this forming method makes it easier to form a chemical bond between the first connection layer and the hardening layer.

[0010] In an optional implementation, the material of the first connection layer includes: silicon Si, titanium Ti, nickel Ni, chromium Cr, silicon oxide SiOx, titanium oxide TiOx, nickel oxide NiOx, chromium oxide CrOx, wherein x is less than or equal to 2, and the material of the hardening layer includes: at least one of acrylic resin and epoxy resin. Among them, silicon oxide SiOx with x less than or equal to 2 can be called oxygen-deficient silicon oxide, and the oxygen-deficient silicon oxide can form silicon oxygen (Si-O) covalent bonds with oxygen atoms of the hardening layer. When the first connection layer includes silicon atoms, the silicon atoms of the first connection layer form silicon oxygen (Si-O) covalent bonds with oxygen atoms of the hardening layer. When the first connection layer includes titanium atoms, the titanium atoms of the first connection layer form titanium oxygen (Ti-O) covalent bonds with oxygen atoms of the hardening layer. When the first connection layer includes nickel-chromium alloy, the nickel atoms of the first connection layer form nickel oxygen (Ni-O) covalent bonds with oxygen atoms of the hardening layer, and / or, the chromium atoms of the first connection layer form chromium oxygen (Cr-O) covalent bonds with oxygen atoms of the hardening layer. Therefore, the first connection layer of various materials can form a covalent bond with the hardened layer, thereby improving the wear resistance of the laminated structure.

[0011] In an optional implementation, the first connecting layer includes Si atoms, the hardening layer includes oxygen atoms, and a silicon Si-oxygen O covalent bond is formed between the hardening layer and the first connecting layer. As a result, the force of the silicon-oxygen covalent bond is stronger, which can further enhance the atomic bonding force between the first connecting layer and the hardening layer, and can further improve the wear resistance of the laminated structure.

[0012] In an optional implementation, the hardened layer includes: a first hardened layer and a second hardened layer stacked, the first hardened layer is connected to the lower surface of the first connecting layer, and the second hardened layer is doped with reinforcing particles. Therefore, the first hardened layer can be pure resin without adding particles, which is conducive to reducing surface roughness, enhancing the connection stability with the first connecting layer, and improving the wear resistance of the laminated structure. The second hardened layer can use particle-reinforced resin to improve the overall rigidity of the hardened layer and enhance the support effect. Therefore, the hardened layer adopts a double-layer structure, which can take into account both wear resistance and support performance.

[0013] In an optional implementation, the material of the reinforcing particles includes: silicon oxide SiO2, zirconium oxide ZrO2, aluminum oxide Al2O3, titanium oxide TiO2, silicon nitride SiN. Thus, by doping the reinforcing particles in the second hardened layer, the rigidity of the hardened layer can be enhanced, and the bending performance of the laminated structure can be improved.

[0014] In an optional implementation, the anti-reflection layer includes: a first low-refractive layer and a first high-refractive layer stacked, and the first high-refractive layer is arranged on the upper surface of the first connecting layer. Thus, by providing the anti-reflection layer, the readability of the display module under strong light can be improved.

[0015] In an optional implementation, the material of the first high-refractive layer includes at least one of zirconium oxide ZrO2, niobium oxide Nb2O5, tantalum pentoxide Ta2O5, aluminum oxide Al2O3, titanium oxide TiO2, silicon nitride Si3N4, silicon oxynitride SiON, and titanium nitride TiN; and the material of the first low-refractive layer includes silicon oxide SiO2. Thus, a chemical bond can be formed between the high-refractive layer and the first connecting layer, thereby enhancing the connection stability between the high-refractive layer and the first connecting layer.

[0016] In an optional implementation, the thickness of the first high refractive layer is in the range of 5-150 nm, and the thickness of the first low refractive layer is in the range of 10-200 nm. Thus, the thickness of the high refractive layer and the low refractive layer is relatively low, which can improve the bending performance of the laminated structure.

[0017] In an optional implementation, the first low-refractive layer is doped with at least one of titanium Ti, zirconium Zr, copper Cu, and aluminum Al; the first high-refractive layer is doped with at least one of yttrium oxide Y2O3, aluminum oxide Al2O3, cerium oxide CeO2, calcium oxide CaO, and magnesium oxide MgO. Thus, by doping the low-refractive layer with metal materials, the hardness of the low-refractive layer can be increased, and the wear resistance of the laminated structure can be improved. By doping the high-refractive layer with toughening materials, the toughness of the high-refractive layer can be increased, and the bending performance of the laminated structure can be improved. In this way, the wear resistance and bending performance of the laminated structure can be taken into account.

[0018] In an optional implementation, the laminate structure further includes: a second connecting layer, the first high-refractive layer is connected to the first low-refractive layer through the second connecting layer, the thickness of the second connecting layer ranges from 1 to 20 atomic layers, the second connecting layer is made of a bondable material, and the bondable material forms a chemical bond with the first high-refractive layer. Thus, by arranging the second connecting layer between the high-refractive layer and the low-refractive layer, a chemical bond is formed between the second connecting layer and the first high-refractive layer, generating a strong bonding force, so that the film layer is not easy to fall off, and the wear resistance of the laminate structure is further improved.

[0019] In an optional implementation, the anti-reflection layer includes N high-refractive layers and N low-reflection layers, and the N high-refractive layers and the N low-reflection layers are arranged alternately, wherein N is an integer greater than or equal to 2. Thus, the anti-reflection layer can be a multi-layer structure, which improves the anti-reflection performance.

[0020] In a second aspect of the embodiment of the present application, an electronic device is provided, comprising a display module and the laminated structure as described above, wherein the laminated structure is arranged on the light-emitting side of the display module. Thus, the display module is provided with the laminated structure, and has better wear resistance.

[0021] The third aspect of the embodiment of the present application provides a method for preparing a laminated structure, including: forming a hardening layer on a base film; performing surface treatment on the side of the hardening layer away from the base film, so that a bond is broken on the side of the hardening layer away from the base film; forming a connecting layer on the hardening layer, the thickness of the first connecting layer is in the range of 1-20 atomic layers, the first connecting layer is made of a bondable material, the thickness of the first connecting layer is in the range of 1-20 atomic layers, the first connecting layer is made of a bondable material, and the bondable material forms a chemical bond with the broken bond of the hardened layer; forming an anti-reflection layer on the connecting layer; forming an anti-fingerprint layer on the anti-reflection layer. As a result, a chemical bond can be formed between the connecting layer and the hardening layer, generating a strong bonding force, making the film layer not easy to fall off, and improving the wear resistance of the laminated structure. In addition, the thickness of the connecting layer is thin, the surface of the hardening layer is smooth, and the wear resistance is better.

[0022] In an optional implementation, the hardening layer includes oxygen atoms, and the connecting layer includes silicon atoms. The silicon atoms of the connecting layer and the oxygen atoms of the hardening layer form silicon-oxygen covalent bonds. Thus, the force of the silicon-oxygen covalent bonds is stronger, which can further enhance the atomic bonding force between the connecting layer and the hardening layer, and can further improve the wear resistance of the laminated structure.

[0023] The embodiment of the present application provides a laminated structure, an electronic device and a method for preparing a laminated structure. The laminated structure can be an optical laminate, and the laminated structure is, for example, arranged on the light-emitting side of a display module. The laminated structure includes: an anti-fingerprint layer, an anti-reflection layer, a connecting layer, a hardening layer and a base film stacked from top to bottom; the hardening layer is arranged on the upper surface of the base film. The connecting layer is, for example, made of a bondable material, and the bondable material forms a chemical bond with the hardening layer. In this way, when the connecting layer is formed on the surface of the hardening layer, a strong chemical bond can be formed between the connecting layer and the hardening layer, so that a strong bonding force is formed between the connecting layer and the hardening layer, thereby improving the wear resistance of the laminated structure. The thickness of the connecting layer is relatively small, for example, 1-20 atomic layers thick, so that a higher proportion of atoms in the connecting layer and the hardening layer undergo cross-linking reactions and bonding, which can further improve the bonding force between the connecting layer and the hardening layer. The surface roughness of the hardening layer on the side away from the base film is, for example, 5-100 nm, so that the surface of the anti-reflection layer prepared on the upper layer is also smooth, further improving the wear resistance of the anti-reflection layer.

[0024] In some embodiments, a connecting layer is provided between the high-refractive index layer and the low-refractive index layer, which can further improve the wear resistance of the laminated structure.

[0025] In some embodiments, the hardening layer may adopt a single-layer resin structure. In other embodiments, the hardening layer may adopt a double-layer structure: the hardening layer close to the connection layer adopts pure resin, and the hardening layer away from the connection layer adopts particle-reinforced resin, which can improve the overall rigidity of the hardening layer and enhance the supporting effect.

[0026] The embodiment of the present application can perform bending reliability test and wear resistance test on laminated structures with different structures, and the bending performance and wear resistance of laminated structures with different structures are measured. It can be concluded that the laminated structure formed by dry process has better wear resistance and bending performance. When the high refractive layer material is zirconium oxide, its modulus is moderate, which can take into account the wear resistance and bending performance of the laminated structure.

[0027] In some embodiments, toughening fillers are added to the high refractive layer to enhance the toughness of the anti-reflective coating, thereby further improving the bending resistance of the laminated structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of the disassembled structure of an electronic device provided in an embodiment of the present application;

[0029] Figure 2A A schematic diagram of the structure of an electronic device provided in an embodiment of the present application;

[0030] Figure 2B A schematic diagram of the structure of another electronic device provided in an embodiment of the present application;

[0031] Figure 3 A schematic diagram of a laminated structure;

[0032] Figure 4 A flow chart of a method for forming an anti-reflection layer by a coating process provided in an embodiment of the present application;

[0033] Figure 5 A schematic diagram of a laminate structure provided in an embodiment of the present application;

[0034] Figure 6 A flow chart of a method for forming an anti-reflection layer by a magnetron sputtering coating process provided in an embodiment of the present application;

[0035] Figure 7 A schematic diagram of another laminate structure provided in an embodiment of the present application;

[0036] Figure 8 A schematic structural diagram of a laminated structure provided in one embodiment of the present application;

[0037] Fig. 9 A schematic structural diagram of a laminated structure provided in another embodiment of the present application;

[0038] Fig.10 A schematic structural diagram of a laminated structure provided in another embodiment of the present application;

[0039] Fig.11 A schematic structural diagram of a laminated structure provided in another embodiment of the present application;

[0040] Fig.12 A schematic structural diagram of a laminated structure provided in another embodiment of the present application;

[0041] Fig.13 A schematic structural diagram of a stacked structure provided in another embodiment of the present application. DETAILED DESCRIPTION

[0042] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.

[0043] In the following, the terms "first", "second", etc. are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.

[0044] In addition, in the present application, directional terms such as "upper" and "lower" are defined relative to the orientation of the components in the drawings. It should be understood that these directional terms are relative concepts. They are used for relative description and clarification, and they can change accordingly according to the changes in the orientation of the components in the drawings.

[0045] The embodiment of the present application provides an electronic device. The electronic device can be a tablet computer, a mobile phone, an e-reader, a remote control, a personal computer (PC), a laptop, a personal digital assistant (PDA), a vehicle-mounted device, an Internet TV, a wearable device, a TV, and other products with a display interface, as well as smart display wearable products such as smart watches and smart bracelets. The embodiment of the present application does not impose any special restrictions on the form of the above-mentioned electronic devices. For the convenience of explanation, the following embodiments are all exemplified by taking the electronic device as a mobile phone as an example.

[0046] like Figure 1 As shown, the electronic device 1 includes a display module 13, a middle frame 11 and a housing (or rear housing) 12. The middle frame 11 is located between the display module 13 and the housing 12.

[0047] The display module 13 is used to display images.

[0048] The display module 13, the middle frame 11 and the housing 12 can be arranged in different layers in the thickness direction of the electronic device, and these layers can be parallel to each other. The plane where each layer is located can be called the XY plane, and the direction perpendicular to the XY plane can be called the Z direction. For example, the display module 13, the middle frame 11 and the housing 12 can be distributed in layers in the Z direction.

[0049] The display module 13 can be Figure 1 The flexible printed circuit (FPC) shown passes through the middle frame 11 and is electrically connected to the PCB disposed on the middle frame 11. Thus, the PCB can transmit display data to the display module 13 to control the display module 13 to display images.

[0050] The middle frame 11 is located between the display module 13 and the housing 12. The surface of the middle frame 11 away from the display module 13 is used to install internal components such as batteries, printed circuit boards (PCB), cameras, antennas, etc. After the housing 12 and the middle frame 11 are covered, the above internal components are located between the housing 12 and the middle frame 11.

[0051] The housing 12 is connected to the middle frame 11 to form a receiving cavity for receiving the above-mentioned PCB, camera, battery and other electronic components, thereby preventing external moisture and dust from invading the receiving cavity and affecting the performance of the above-mentioned electronic components.

[0052] The embodiments of the present application do not limit the structure of the mobile phone. In some embodiments of the present application, such as Figure 2A , Figure 2B As shown, the mobile phone can be a foldable screen mobile phone, and the display module 13 of the foldable screen is foldable.

[0053] The embodiment of the present application does not limit the type of the folding screen mobile phone. In some embodiments, such as Figure 2A As shown, the foldable screen mobile phone adopts an external folding design. When the foldable screen mobile phone is in a folded state, the display module 13 is located on the outside of the device.

[0054] In other embodiments, Figure 2B As shown, the foldable screen mobile phone adopts an inward folding design. When the foldable screen mobile phone is in a bent state, the display module 13 is located on the inner side of the device.

[0055] The display module 13 may be an active matrix organic light-emitting diode (AMOLED) display screen.

[0056] As a self-luminous display, the AMOLED display screen does not need a backlight module (BLM). Therefore, when the base substrate in the AMOLED display screen is made of a flexible resin material, such as polyimide (PI) or polyethylene terephthalate (PET), the AMOLED display screen can have a bendable property.

[0057] In some embodiments, in order to improve the reading experience of the screen under sunlight or strong light, an anti-reflection (AR) film may also be provided on the light emitting surface of the display module 13 .

[0058] For example, Figure 3 As shown, a laminated structure 10 is disposed on the light emitting surface of the display module 13 . The laminated structure may be an optical laminate, and the laminated structure may include, for example, an anti-reflection layer. The laminated structure may improve the readability of the display module under strong light.

[0059] In some embodiments, the laminated structure 10 includes: a substrate, a hardening layer, a high-refractive layer, a low-refractive layer, and an anti-fingerprint layer that are stacked.

[0060] The embodiment of the present application does not limit the number of layers of the low-refractive layer and the high-refractive layer, and only requires that the low-refractive layer and the high-refractive layer are arranged alternately. In some embodiments, the anti-reflection layer includes two low-refractive layers and two high-refractive layers, and the low-refractive layers and the high-refractive layers are arranged alternately. The high-refractive material includes metal oxides such as niobium pentoxide and zirconium oxide, and the low-refractive material includes materials such as silicon oxide.

[0061] The present application embodiment does not limit the preparation process of the anti-reflection layer. In some embodiments, the anti-reflection layer can be formed by a coating process (also known as a "wet AR film").

[0062] The coating process refers to coating the resin material containing high refractive index and low refractive index particles on the surface of the substrate by slit coating or micro-concave coating, respectively, to form a high refractive index material film layer and a low refractive index material film layer. The filling particles in the high refractive index material film layer include: metal oxide nanoparticles such as aluminum oxide, zirconium oxide, and tin oxide, and the filling particles in the low refractive index layer include: hollow silica nanoparticles. Figure 4 This is a flow chart of a method for forming an anti-reflection layer through a coating process provided in an embodiment of the present application. Figure 4 As shown, the method includes:

[0063] S1. Substrate surface treatment.

[0064] Among them, the substrate may be surface treated.

[0065] S2. Hardening layer coating.

[0066] Here, a hardening layer may be coated on the surface of the substrate.

[0067] S3. High refractive layer coating.

[0068] Wherein, a high refractive layer may be coated on the surface of the hardened layer, and the high refractive layer may be cured.

[0069] S4. Low refractive layer coating.

[0070] Wherein, a low-refractive layer may be formed on the surface of the cured high-refractive layer, and the low-refractive layer may be cured.

[0071] However, the anti-reflection layer formed by the wet process has poor wear resistance. The friction of the protective film during use by the user can easily cause the anti-reflection layer to be scratched or fall off, resulting in surface discoloration and poor user experience.

[0072] To this end, an embodiment of the present application provides a film layer that can effectively improve the wear resistance and reliability of the anti-reflection layer.

[0073] The present application does not limit the position of the film layer in the display module. In some embodiments, the film layer can be arranged on the light-emitting side of the display module. The film layer can be a laminated structure including multiple laminated layers.

[0074] Figure 5 A schematic diagram of a stacked structure provided in an embodiment of the present application.

[0075] like Figure 5 As shown, the laminated structure 10 includes: Figure 5 The anti-fingerprint layer 101, the anti-reflection layer 100, the connecting layer 1001, the hardening layer 104 and the base film 105 are stacked (in the -z direction as shown); the hardening layer 104 is arranged on the upper surface of the base film 105.

[0076] The surface roughness of the hardened layer 104 on the side away from the base film is 5-100 nm. Thus, the surface of the hardened layer 104 is smoother, so that the surface of the anti-reflection layer prepared on the upper layer is also smooth, thereby improving the wear resistance of the anti-reflection layer.

[0077] The connecting layer 1001 can be the first connecting layer. The connecting layer 1001 is made of a bonding material, and the bonding material forms a chemical bond with the hardened layer 104. In this way, when the connecting layer 1001 is formed on the surface of the hardened layer 104, a strong chemical bond can be formed between the connecting layer 1001 and the hardened layer 104, thereby forming a strong bonding force between the connecting layer 1001 and the hardened layer 104, further improving the wear resistance.

[0078] The chemical bond may be formed by bonding.

[0079] The thickness of the connecting layer 1001 is in the range of 1-20 atomic layers. When the connecting layer 1001 includes silicon atoms, the thickness thereof is in the range of 1-20 silicon atoms, so that a higher proportion of atoms in the connecting layer 1001 undergo cross-linking reaction and bonding with the hardening layer 104, which can further improve the bonding force between the connecting layer 1001 and the hardening layer 104.

[0080] In some embodiments, the thickness of the connecting layer 1001 is in the range of 1-5 atomic layers. When the connecting layer 1001 includes silicon atoms, the thickness thereof is in the range of 1-5 silicon atoms, which can further reduce the thickness of the connecting layer 1001, improve the light transmittance of the connecting layer 1001, and improve the bonding force between the connecting layer 1001 and the hardening layer 104.

[0081] The embodiment of the present application does not limit the type of chemical bond between the hardening layer 104 and the connecting layer 1001. Among them, chemical bonds include: ionic bonds, covalent bonds, and metallic bonds. Ionic bonds can be formed by electrostatic action through the transfer of electrons between atoms to form positive and negative ions. Covalent bonds can be formed by sharing one or more pairs of electrons between atoms. Metallic bonds are a modified covalent bond that can be formed by multiple atoms sharing some free-flowing electrons. In some embodiments, the connecting layer 1001 is made of a bondable material, and the hardening layer 104 is bonded to the bondable material through a covalent bond.

[0082] The laminated structure provided in the embodiment of the present application connects the hardening layer 104 and the anti-reflection layer through the connecting layer 1001, and the connecting layer 1001 is made of a bondable material, which forms a chemical bond with the hardening layer 104, generating a strong bonding force, making the film layer not easy to fall off, and improving the wear resistance of the laminated structure. In addition, the connecting layer 1001 is thin and the surface of the hardening layer 104 is smooth, so the wear resistance is better.

[0083] The present application embodiment does not limit the material of the base film 105. In some embodiments, the material of the base film 105 includes: at least one of polyethylene terephthalate PET, thermoplastic polyurethane elastomer rubber TPU, and polyimide PI.

[0084] The embodiment of the present application does not limit the materials of the hardening layer 104 and the connecting layer 1001. In some embodiments, the hardening layer 104 includes oxygen atoms, and the connecting layer 1001 forms covalent bonds with the oxygen atoms of the hardening layer 104.

[0085] In some embodiments, the material of the connection layer 1001 includes silicon Si, titanium Ti, nickel Ni, chromium Cr, silicon oxide SiOx, titanium oxide TiOx, nickel oxide NiOx, and chromium oxide CrOx, where x is less than or equal to 2.

[0086] The silicon oxide SiOx with x less than or equal to 2 may be referred to as oxygen-deficient silicon oxide, and the oxygen-deficient silicon oxide may form silicon-oxygen (Si—O) covalent bonds with oxygen atoms of the hardening layer 104 .

[0087] When the connection layer 1001 includes silicon atoms, the silicon atoms of the connection layer 1001 and the oxygen atoms of the hardening layer 104 form silicon-oxygen (Si—O) covalent bonds.

[0088] When the connection layer 1001 includes titanium atoms, the titanium atoms of the connection layer 1001 and the oxygen atoms of the hardening layer 104 form titanium-oxygen (Ti—O) covalent bonds.

[0089] When the connecting layer 1001 includes a nickel-chromium alloy, the nickel atoms of the connecting layer 1001 form nickel-oxygen (Ni—O) covalent bonds with the oxygen atoms of the hardening layer 104, and / or the chromium atoms of the connecting layer 1001 form chromium-oxygen (Cr—O) covalent bonds with the oxygen atoms of the hardening layer 104.

[0090] In the present application, when the connection layer 1001 includes silicon atoms, the thickness of the connection layer 1001 in the present application is, for example, less than 1 nm, so that the influence of the connection layer 1001 on the transmittance can be reduced.

[0091] The embodiments of the present application do not limit the forming method of the stacked structure. In some embodiments, the stacked structure can be deposited using a magnetron sputtering coating process (also known as a "dry AR film").

[0092] Figure 6 This is a flow chart of a method for forming an anti-reflection layer 100 by a magnetron sputtering coating process provided in an embodiment of the present application. Figure 6 As shown, the method for preparing the anti-reflection layer 100 includes:

[0093] S11 . Forming a hardening layer 104 on the base film 105 .

[0094] Before forming the hardening layer 104 on the base film 105 , the base film 105 may be surface treated.

[0095] The hardening layer 104 may be formed on the base film 105 by coating the hardening layer 104 on the surface of the base film 105 and curing the hardening layer 104 .

[0096] The magnetron sputtering coating process refers to applying a DC voltage between the coating target and the substrate under vacuum conditions. The voltage decomposes the gas into argon ions (Ar+) and electrons, causing the positively charged ions to be accelerated and collide with the coating target, sputtering the coating target atoms through momentum transfer.

[0097] For example, the surface of the coating target can be vaporized into gaseous atoms, molecules or partially ionized into ions and electrons through electrodes, and a magnetic field is introduced on the surface of the coating target. Under the action of the electric field, the electrons collide with argon atoms in the process of flying toward the substrate, causing them to ionize and produce Ar+ and new electrons. The new electrons fly toward the substrate, and the Ar+ is accelerated to fly toward the cathode coating target under the action of the electric field, and bombards the surface of the coating target with high energy, causing the coating target to sputter. Among the sputtered particles, neutral target atoms or molecules are deposited on the substrate to form a thin film.

[0098] S12. Performing surface treatment on the side of the hardened layer 104 facing away from the base film.

[0099] After the hardening layer 104 is cured, a surface activation treatment may be performed on a side of the hardening layer 104 facing away from the base film.

[0100] In this embodiment, the surface activation treatment of the hardened layer 104 may be performed by high-energy ion beam etching on the surface of the hardened layer 104 away from the base film, so that bonds are broken on the hardened layer 104 away from the base film.

[0101] S13 . Forming a connection layer 1001 on the hardened layer 104 .

[0102] The connection layer 1001 may be formed on the surface of the hardening layer 104 by chemical vapor deposition or physical vapor deposition, and the connection layer 1001 forms chemical bonds with the broken bonds of the hardening layer 104 .

[0103] For example, the material of the connecting layer 1001 includes: silicon, silicon oxide SiOx, titanium Ti, nickel-chromium alloy NiCr, wherein x is less than or equal to 2. The thickness of the connecting layer 1001 ranges from 1 to 20 atomic layers. When the connecting layer 1001 includes silicon atoms, its thickness ranges from 1 to 20 silicon atoms. The connecting layer is made of a bondable material, and the bondable material forms a chemical bond with the broken bond of the hardened layer.

[0104] S14. forming an anti-reflection layer on the connecting layer 1001;

[0105] The anti-reflection layer may be formed on the surface of the connection layer 1001 by magnetron sputtering. In some embodiments, the anti-reflection layer includes: a high-refractive layer and a low-refractive layer stacked.

[0106] When forming the anti-reflection layer, a high refractive layer can be formed on the surface of the connecting layer 1001, and a low refractive layer can be formed on the surface of the high refractive layer, forming a stacked structure design of the low refractive layer and the high refractive layer.

[0107] In this embodiment, the connection layer 1001 , the high refractive layer, and the low refractive layer are all formed by, for example, a magnetron sputtering coating process.

[0108] S15. Forming an anti-fingerprint layer on the anti-reflection layer.

[0109] Wherein, an anti-fingerprint layer can be formed on the surface of the low-refractive layer by an AF coating process. The anti-fingerprint layer can be formed by coating, spraying or evaporation. In some embodiments, the low-refractive layer resin contains the anti-fingerprint layer.

[0110] In the present application, the anti-fingerprint layer is formed by the AF coating process, which can be formed by spraying or evaporating AF liquid. Among them, the AF liquid contains fluorosilane, which is a hydrophobic and oleophobic polymer. The AF liquid forms a film layer with the glass surface (Si-O chemical bonds produce chemical links). The naked eye cannot recognize the existence of this invisible film layer, which does not affect the visual effect of the screen.

[0111] Among them, AF liquid is a surface treatment agent that can be used for waterproof and oil-proof surface treatment of touch screens to reduce dust and fingerprints adhering to the surface. AF liquid can be applied to various substrates, including touch screen glass panels (mobile phones, monitors, etc.), glass products, plastics, metal products, etc. AF liquid has excellent waterproof and anti-fouling effects and can effectively prevent surface scratches.

[0112] The embodiment of the present application does not limit the structure of the hardening layer 104. In some embodiments, the hardening layer 104 is a single-layer structure. The material of the hardening layer 104 includes: at least one of acrylic resin and epoxy resin.

[0113] In other embodiments, Figure 7 As shown, the hardening layer 104 includes: a first hardening layer 1041 and a second hardening layer 1042 which are stacked, the first hardening layer 1041 is connected to the connection layer 1001, and the first hardening layer 1041 can be pure resin without adding particles, which is conducive to reducing surface roughness, enhancing the connection stability with the connection layer 1001, and improving the wear resistance of the laminated structure. The second hardening layer 1042 can be made of particle-reinforced resin, for example, the second hardening layer 1042 is added with: silicon oxide SiO2, zirconium oxide ZrO2, aluminum oxide Al2O3, titanium oxide TiO2, silicon nitride SiN, which improves the overall rigidity of the hardening layer 104 and enhances the supporting effect. Among them, the roughness of the first hardening layer 1041 is lower than that of the second hardening layer 1042.

[0114] The hardening layer 104 provided in this embodiment adopts a double-layer structure, which can take into account both wear resistance and support performance.

[0115] The structure of the anti-reflection layer is not limited in the embodiment of the present application. In some embodiments, the anti-reflection layer 100 includes: a low-refractive layer 102 and a high-refractive layer 103 which are stacked, and the high-refractive layer 103 is disposed on the upper surface of the connecting layer 1001 .

[0116] The embodiment of the present application does not limit the materials of the high refractive layer 103 and the low refractive layer 102. The material of the high refractive layer 103 includes at least one of zirconium oxide ZrO2, niobium oxide Nb2O5, tantalum pentoxide Ta2O5, aluminum oxide Al2O3, titanium oxide TiO2, silicon nitride Si3N4, silicon oxynitride SiON, and titanium nitride TiN.

[0117] The material of the low refractive layer 102 includes silicon oxide SiO2.

[0118] In some embodiments, the low-refractive layer 102 is doped with at least one of metal elements such as titanium Ti, zirconium Zr, copper Cu, and aluminum Al.

[0119] The anti-reflection layer provided in this embodiment can increase the hardness of the low-refractive layer by doping the metal material into the low-refractive layer.

[0120] The high refractive layer 103 is doped with at least one of yttrium oxide Y2O3, aluminum oxide Al2O3, cerium oxide CeO2, calcium oxide CaO, and magnesium oxide MgO.

[0121] The anti-reflection layer provided in this embodiment can increase the toughness of the high-refractive layer by doping the high-refractive layer with a toughening material.

[0122] The embodiment of the present application does not limit the connection method between the high-refractive layer 103 and the low-refractive layer 102. In some embodiments, the low-refractive layer 102 can be formed on the upper surface of the high-refractive layer 103 by a magnetron sputtering coating process.

[0123] In other embodiments, Fig.11 As shown, the laminated structure further includes a connecting layer 1002, which can be a second connecting layer. The connecting layer 1002 is arranged between the low-refractive layer 102 and the high-refractive layer 103. The low-refractive layer 102 is connected to the high-refractive layer 103 through the connecting layer 1002. The thickness of the connecting layer 1002 ranges from 1 to 20 atomic layers. The connecting layer 1002 is made of a bondable material, and the bondable material forms a chemical bond with the high-refractive layer 103.

[0124] The material and structure of the bondable material may refer to the description of the above-mentioned bondable material, which will not be repeated here.

[0125] The embodiments of the present application do not limit the number of layers of the anti-reflection layer. In some embodiments, the anti-reflection layer includes N high-refractive layers and N low-reflective layers, and the N high-refractive layers and the N low-reflective layers are arranged at intervals, where N is an integer greater than or equal to 2.

[0126] In some embodiments, a connection layer 1001 may be disposed between adjacent high-refractive layers and low-refractive layers. The structure of the connection layer 1001 may refer to the description of the connection layer 1001 described above.

[0127] In the present application, the bending performance and wear resistance of the laminated structure are related to the molding process of the laminated structure and the material and thickness of the laminated layers.

[0128] The embodiments of the present application can perform bending reliability tests and wear resistance tests on laminated structures with different structures, and measure the bending performance and wear resistance of laminated structures with different structures.

[0129] The bending test may be to bend the laminate structure to obtain a single-unit limiting bending radius of the laminate structure. The smaller the single-unit limiting bending radius of the laminate structure is, the better the bending performance is.

[0130] The wear resistance test may be to rub the surface of the laminate structure with steel wool to obtain the number of times the laminate structure can resist steel wool friction. The more times the laminate structure can resist steel wool friction, the better the wear resistance.

[0131] In some embodiments, the laminated structure is formed by a wet coating process, the high refractive layer is made of ZrO2, there is no connecting layer, the hardening layer 104 is a single-layer structure, the steel wool friction resistance is 1000-2000 times, and the single body limit bending radius is 0.15mm. The wear resistance is poor, but the bending performance is good.

[0132] In some embodiments, the laminated structure is formed by a dry coating process, the material of the high refractive layer is ZrO2, the material of the connecting layer 1001 is Si, and the thickness of the connecting layer 1001 ranges from 1 to 20 atomic layers, and the hardening layer 104 adopts a single-layer resin structure. The number of steel wool friction resistance is greater than or equal to 5000 times, and the monomer limit bending radius is 0.25mm. The laminated structure of this embodiment is formed by a dry process and is provided with a connecting layer 1001. The wear resistance and bending performance are both excellent, and both wear resistance and bending performance can be taken into account.

[0133] In some embodiments, the laminated structure is formed by a dry coating process, the material of the high refractive layer is ZrO2, the material of the connecting layer 1001 is Si, and the thickness of the connecting layer 1001 ranges from 1 to 20 atomic layers, and the hardened layer 104 includes: a first hardened layer 1041 and a second hardened layer 1042 which are stacked, the first hardened layer 1041 can be pure resin without adding particles, and the second hardened layer 1042 can be particle-reinforced resin, for example, the second hardened layer 1042 is added with: SiO2. The number of steel wool friction resistance is greater than or equal to 6000 times, and the monomer limit bending radius is 0.25mm. In the laminated structure provided in this embodiment, the hardened layer 104 adopts a double-layer structure: a pure resin layer and a particle-reinforced resin layer, which can further improve the wear resistance of the laminated structure.

[0134] In some embodiments, the laminated structure is formed by a dry coating process, the material of the high refractive layer is Nb2O5, the material of the connecting layer 1001 is Si, and the thickness of the connecting layer 1001 ranges from 1 to 20 atomic layers, the hardening layer 104 is a single-layer resin structure, the number of steel wool friction resistance is 2000-3000 times, and the monomer limit bending radius is 0.5mm. In the laminated structure provided in this embodiment, the high refractive layer material is Nb2O5, and compared with the high refractive layer material using ZrO2, the wear resistance and bending performance are both reduced. When the high refractive layer is ZrO2, the modulus is moderate, the material with too low modulus has poor wear resistance, and the material with too high modulus has poor bending performance.

[0135] In some embodiments, the laminated structure is formed by a dry coating process, the material of the high refractive layer is ZrO2, the connection layer 1001 is not provided, the hardening layer 104 is a single-layer resin structure, the number of steel wool friction resistance is 1000 times, and the single body limit bending radius is 1.5 mm. The laminated structure of this embodiment is not provided with a connection layer 1001, and compared with the laminated structure provided with a connection layer 1001, the wear resistance and bending performance are poor.

[0136] In some embodiments, the laminated structure is formed by a dry coating process, the material of the high refractive layer is ZrO2, the material of the connecting layer 1001 is Si, and the thickness of the connecting layer 1001 is greater than 20 atomic layers, the hardening layer 104 is a single-layer resin structure, the number of steel wool friction resistance is about 3000 times, and the monomer limit bending radius is 0.4mm. In the laminated structure provided in this embodiment, the thickness of the connecting layer 1001 is relatively thick, and the wear resistance and bending performance are reduced.

[0137] In the above embodiments, the correlation between the bending performance and wear resistance of the laminated structure and the molding process of the laminated structure, the thickness of the connecting layer 1001, and the material of the high refractive layer can be obtained.

[0138] The structures that may affect the bending performance and wear resistance of the laminated structure are described below in conjunction with the embodiments.

[0139] Figure 8 This is a schematic diagram of a stacked structure provided by an embodiment of the present application. Figure 8 As shown, the laminated structure includes: an anti-fingerprint layer 101, an anti-reflection layer 100, a connecting layer 1001, a hardening layer 104 and a base film 105 stacked from top to bottom; the hardening layer 104 is arranged on the base film 105, the connecting layer 1001 is formed on the hardening layer 104, the anti-reflection layer 100 is formed on the connecting layer 1001, and the anti-fingerprint layer 101 is formed on the anti-reflection layer 100.

[0140] The connection layer 1001 is formed on the hardening layer 104 by magnetron sputtering. The thickness of the connection layer 1001 is in the range of 1-20 atomic layers. For example, the thickness of the connection layer 1001 is in the range of 1-5 Si atomic layers.

[0141] The anti-reflection layer 100 includes a high-refractive layer 103 and a low-refractive layer 102 which are stacked. The high-refractive layer 103 is formed on the connecting layer 1001 , and the low-refractive layer 102 is formed on the high-refractive layer 103 .

[0142] The material of the high refractive layer 103 is ZrO2, and the thickness of the high refractive layer 103 is in the range of 5-150 nm. The material of the low refractive layer 102 is SiO2, and the thickness of the low refractive layer 102 is in the range of 10-200 nm. The hardening layer 104 may be a hard coating (HC) layer.

[0143] The high refractive layer 103 and the low refractive layer 102 can be formed by magnetron sputtering.

[0144] The wear resistance and bending performance tests of the laminated structure were carried out. When the laminated structure was rubbed with steel wool ≥5000 times, there was no obvious scratch on the coating (anti-reflection layer), the single-body bending resistance limit radius R of the laminated structure was less than or equal to 0.25 mm, and the coating had no cracks.

[0145] The laminated structure provided in this embodiment has excellent wear resistance and bending resistance.

[0146] Fig. 9 FIG. 1 is a schematic diagram of a laminate structure provided in another embodiment of the present application. Fig. 9 As shown, the laminated structure includes: an anti-fingerprint layer 101, an anti-reflection layer 100, a connecting layer 1001, a hardening layer 104 and a base film 105 stacked from top to bottom; the hardening layer 104 is arranged on the base film 105, the connecting layer 1001 is formed on the hardening layer 104, the anti-reflection layer 100 is formed on the connecting layer 1001, and the anti-fingerprint layer 101 is formed on the anti-reflection layer 100.

[0147] The connection layer 1001 is formed on the hardening layer 104 by magnetron sputtering. The thickness of the connection layer 1001 is less than 1 nm. For example, the thickness of the connection layer 1001 ranges from 1 to 5 Si atomic layers.

[0148] The anti-reflection layer 100 comprises: N layers of high refractive index layers and N layers of low reflective index layers stacked, the N layers of high refractive index layers and the N layers of low reflective index layers being arranged at intervals, and the low refractive index layer 102 being formed on the high refractive index layer 103. Wherein, N is a positive integer greater than or equal to 2.

[0149] The material of the high refractive layer is ZrO2, and the thickness of the high refractive layer is in the range of 5-150 nm. The material of the low refractive layer is SiO2, and the thickness of the low refractive layer 102 is in the range of 10-200 nm.

[0150] The high-refractive layer and the low-refractive layer can be formed by magnetron sputtering.

[0151] The wear resistance and bending performance tests of the laminated structure are carried out. When the laminated structure is rubbed with steel wool ≥5000 times, there is no obvious scratch on the coating (anti-reflection layer), the single-body bending resistance limit radius R of the laminated structure is less than or equal to 0.25mm, and the coating has no cracks and reflectivity.

[0152] The laminated structure provided in this embodiment refers to Figure 8 In the laminated structure shown, the number of anti-reflection layers is increased, the wear resistance and bending resistance remain unchanged, and the anti-reflection effect is better.

[0153] Fig.10 FIG. 1 is a schematic diagram of a laminate structure provided in another embodiment of the present application. Fig.10 As shown, the laminated structure includes: an anti-fingerprint layer 101, an anti-reflection layer 100, a connecting layer 1001, a hardening layer 104 and a base film 105 stacked from top to bottom; the hardening layer 104 is arranged on the base film 105, the connecting layer 1001 is formed on the hardening layer 104, the anti-reflection layer 100 is formed on the connecting layer 1001, and the anti-fingerprint layer 101 is formed on the anti-reflection layer 100.

[0154] The connection layer 1001 is formed on the hardening layer 104 by magnetron sputtering. The thickness of the connection layer 1001 is less than 1 nm. For example, the thickness of the connection layer 1001 ranges from 1 to 5 Si atomic layers.

[0155] The anti-reflection layer 100 includes a high-refractive layer 103 and a low-refractive layer 102 which are stacked. The high-refractive layer 103 is formed on the connecting layer 1001 , and the low-refractive layer 102 is formed on the high-refractive layer 103 .

[0156] In this embodiment, the material of the high refractive layer 103 is ZrO2, and the high refractive layer 103 is doped with at least one of Y2O3, Al2O3, CeO2, and CaO. The thickness of the high refractive layer 103 is in the range of 5-150 nm. The material of the low refractive layer 102 is SiO2, and at least one of the metal elements such as Ti, Zr, Cu, and Al is doped with the low refractive layer 102. The thickness of the low refractive layer 102 is in the range of 10-200 nm.

[0157] The high refractive layer 103 and the low refractive layer 102 can be formed by magnetron sputtering.

[0158] The wear resistance and bending performance tests of the laminated structure were carried out. When the laminated structure was rubbed with steel wool ≥5000 times, there was no obvious scratch on the coating (anti-reflection layer), the single-body bending resistance limit radius R of the laminated structure was less than or equal to 0.2 mm, and the coating had no cracks.

[0159] The laminated structure provided in this embodiment has excellent wear resistance and bending resistance. By filling the high refractive layer with toughening filler, the toughness of the anti-reflection coating is enhanced, further improving the bending resistance of the laminated structure.

[0160] Fig.11 FIG. 1 is a schematic diagram of a laminate structure provided in another embodiment of the present application. Fig.11 As shown, the laminated structure includes: an anti-fingerprint layer 101, a low-refractive layer 102, a connecting layer 1002, a high-refractive layer 103, a connecting layer 1001, a hardening layer 104 and a base film 105 stacked from top to bottom; the hardening layer 104 is arranged on the base film 105, the connecting layer 1001 is formed on the hardening layer 104, the anti-reflection layer 100 is formed on the connecting layer 1001, and the anti-fingerprint layer 101 is formed on the anti-reflection layer 100.

[0161] The connection layer 1001 is formed on the hardening layer 104 by magnetron sputtering. The thickness of the connection layer 1001 is less than 1 nm. For example, the thickness of the connection layer 1001 ranges from 1 to 5 Si atomic layers.

[0162] The material of the high refractive layer 103 is ZrO2, and the thickness of the high refractive layer 103 is in the range of 5-150 nm. The material of the low refractive layer 102 is SiO2, and the thickness of the low refractive layer 102 is in the range of 10-200 nm.

[0163] The high refractive layer 103 and the low refractive layer 102 can be formed by magnetron sputtering.

[0164] The wear resistance and bending performance tests of the laminated structure were carried out. When the laminated structure was rubbed with steel wool for ≥ 6000 times, there was no obvious scratch on the coating (anti-reflection layer), the single-body bending resistance limit radius R of the laminated structure was less than or equal to 0.2 mm, and the coating had no cracks.

[0165] The laminated structure provided in this embodiment refers to Figure 8 In the laminated structure shown, a connecting layer 1002 is added in this embodiment, so that the bonding force between the coatings is enhanced, and the wear resistance and bending resistance are further improved.

[0166] Fig.12 FIG. 1 is a schematic diagram of a laminate structure provided in another embodiment of the present application. Fig.12As shown, the laminated structure includes: an anti-fingerprint layer 101, an anti-reflection layer 100, a connecting layer 1001, a hardening layer 104 and a base film 105 stacked from top to bottom; the hardening layer 104 is arranged on the base film 105, the connecting layer 1001 is formed on the hardening layer 104, the anti-reflection layer 100 is formed on the connecting layer 1001, and the anti-fingerprint layer 101 is formed on the anti-reflection layer 100.

[0167] The connection layer 1001 is formed on the hardening layer 104 by magnetron sputtering. The thickness of the connection layer 1001 is less than 1 nm. For example, the thickness of the connection layer 1001 ranges from 1 to 5 Si atomic layers.

[0168] The anti-reflection layer 100 includes a high-refractive layer 103 and a low-refractive layer 102 which are stacked. The high-refractive layer 103 is formed on the connecting layer 1001 , and the low-refractive layer 102 is formed on the high-refractive layer 103 .

[0169] The material of the high refractive layer 103 includes at least one of Ta2O5, Si3N4, TiO2, Al2O3 and TiN, and the thickness of the high refractive layer 103 is in the range of 5-150nm. The material of the low refractive layer 102 is SiO2, and the thickness of the low refractive layer 102 is in the range of 10-200nm.

[0170] The high refractive layer 103 and the low refractive layer 102 can be formed by magnetron sputtering.

[0171] The wear resistance and bending performance tests of the laminated structure were carried out. When the laminated structure was rubbed with steel wool ≥3000 times, there was no obvious scratch on the coating (anti-reflection layer), the single-body bending resistance limit radius R of the laminated structure was less than or equal to 0.3 mm, and the coating had no cracks.

[0172] The laminated structure provided in this embodiment has a material of a high refractive layer and Figure 8 The high refractive layer shown has different materials, and the wear resistance and bending resistance are reduced. Among them, when the high refractive layer is ZrO2, the modulus is moderate, the material with too low modulus has poor wear resistance, and the material with too high modulus has poor bending.

[0173] Fig.13 FIG. 1 is a schematic diagram of a laminate structure provided in another embodiment of the present application. Fig.13 As shown, the laminated structure includes: an anti-fingerprint layer 101, an anti-reflection layer 100, a connecting layer 1001, a hardening layer 104 and a base film 105 stacked from top to bottom; the hardening layer 104 is arranged on the base film 105, the connecting layer 1001 is formed on the hardening layer 104, the anti-reflection layer 100 is formed on the connecting layer 1001, and the anti-fingerprint layer 101 is formed on the anti-reflection layer 100.

[0174] The connection layer 1001 is formed on the hardening layer 104 by magnetron sputtering. The material of the connection layer 1001 includes at least one of SiOx (X≤2), Ti, and NiCr. The thickness of the connection layer 1001 is less than 1 nm.

[0175] The anti-reflection layer 100 includes a high-refractive layer 103 and a low-refractive layer 102 which are stacked. The high-refractive layer 103 is formed on the connecting layer 1001 , and the low-refractive layer 102 is formed on the high-refractive layer 103 .

[0176] The material of the high refractive layer 103 includes at least one of Ta2O5, Si3N4, TiO2, Al2O3 and TiN, and the thickness of the high refractive layer 103 is in the range of 5-150nm. The material of the low refractive layer 102 is SiO2, and the thickness of the low refractive layer 102 is in the range of 10-200nm.

[0177] The high refractive layer 103 and the low refractive layer 102 can be formed by magnetron sputtering.

[0178] The wear resistance and bending performance tests of the laminated structure were carried out. When the laminated structure was rubbed with steel wool ≥3000 times, there was no obvious scratch on the coating (anti-reflection layer), the single-body bending resistance limit radius R of the laminated structure was less than or equal to 0.3 mm, and the coating had no cracks.

[0179] The laminated structure provided in this embodiment has a material of the connecting layer 1001 and Figure 8 The connecting layer 1001 shown is made of different materials, and its wear resistance and bending resistance are reduced.

[0180] The embodiment of the present application provides a laminated structure, an electronic device and a method for preparing the laminated structure. The laminated structure can be an optical laminate, and the laminated structure is, for example, arranged on the light-emitting side of a display module. The laminated structure includes: an anti-fingerprint layer, an anti-reflection layer, a connecting layer, a hardening layer and a base film stacked from top to bottom; the hardening layer is arranged on the upper surface of the base film. The connecting layer is, for example, made of a bondable material, and the bondable material forms a chemical bond with the hardening layer. In this way, when the connecting layer is formed on the surface of the hardening layer, a strong chemical bond can be formed between the connecting layer and the hardening layer, so that a strong bonding force is formed between the connecting layer and the hardening layer, thereby improving the wear resistance of the laminated structure. The thickness of the connecting layer is relatively small, for example, 1-20 atomic layers thick, so that a higher proportion of atoms in the connecting layer and the hardening layer undergo cross-linking reactions and bonding, which can further improve the bonding force between the connecting layer and the hardening layer. The surface of the hardening layer facing away from the base film is smoother, and the surface roughness is, for example, 5-100nm, which further improves the wear resistance of the hardening layer.

[0181] In some embodiments, a connecting layer is provided between the high-refractive index layer and the low-refractive index layer, which can further improve the wear resistance of the laminated structure.

[0182] In some embodiments, the hardening layer may adopt a single-layer resin structure. In other embodiments, the hardening layer may adopt a double-layer structure: the hardening layer close to the connection layer adopts pure resin, and the hardening layer away from the connection layer adopts particle-reinforced resin, which can improve the overall rigidity of the hardening layer and enhance the supporting effect.

[0183] The embodiment of the present application can perform bending reliability test and wear resistance test on laminated structures with different structures, and the bending performance and wear resistance of laminated structures with different structures are measured. It can be concluded that the laminated structure formed by dry process has better wear resistance and bending performance. When the high refractive layer material is zirconium oxide, its modulus is moderate, which can take into account the wear resistance and bending performance of the laminated structure.

[0184] In some embodiments, toughening fillers are added to the high refractive layer to enhance the toughness of the anti-reflective coating, thereby further improving the bending resistance of the laminated structure.

[0185] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A laminated structure, characterized in that: The laminated structure is arranged on the display module, and the laminated structure comprises: an anti-fingerprint layer, an anti-reflection layer, a first connection layer, a hardening layer and a base film which are stacked; The hardened layer is arranged on the base film, the surface roughness of the hardened layer on the side away from the base film is 5-100nm, the thickness of the first connecting layer ranges from 1-20 atomic layers, the first connecting layer is made of a bondable material, and the bondable material forms a chemical bond with the hardened layer.

2. The laminated structure according to claim 1, characterized in that: The chemical bond formed between the hardened layer and the bondable material includes: a covalent bond.

3. The laminated structure according to claim 2, characterized in that: The bondable material includes silicon atoms, the material of the hardened layer includes oxygen atoms, and the covalent bond formed between the hardened layer and the bondable material includes a silicon-oxygen covalent bond.

4. The laminated structure according to any one of claims 1 to 3, characterized in that: The first connection layer includes silicon atoms, and the thickness of the first connection layer ranges from 1 to 5 silicon atomic layers.

5. The laminated structure according to any one of claims 1 to 4, characterized in that: The first connection layer is formed on the hardening layer by chemical vapor deposition or physical vapor deposition to form the chemical bond.

6. The laminated structure according to any one of claims 1 to 5, characterized in that: The material of the first connection layer includes: silicon Si, titanium Ti, nickel Ni, chromium Cr, silicon oxide SiOx, titanium oxide TiOx, nickel oxide NiOx, chromium oxide CrOx, wherein x is less than or equal to 2, and the material of the hardening layer includes: at least one of acrylic resin and epoxy resin.

7. The laminated structure according to any one of claims 1 to 6, characterized in that: The hardened layer includes: a first hardened layer and a second hardened layer which are stacked, the first hardened layer is connected to the first connecting layer, and the second hardened layer is doped with strengthening particles.

8. The laminated structure according to claim 7, characterized in that: The strengthening particles include silicon oxide SiO2, zirconium oxide ZrO2, aluminum oxide Al2O3, titanium oxide TiO2, and silicon nitride SiN.

9. The laminated structure according to any one of claims 1 to 6, characterized in that: The anti-reflection layer includes: a first low-refractive layer and a first high-refractive layer which are stacked, and the first high-refractive layer is connected to the first connecting layer.

10. The laminated structure according to claim 9, characterized in that: The material of the first high refractive layer includes at least one of zirconium oxide ZrO2, niobium oxide Nb2O5, tantalum pentoxide Ta2O5, aluminum oxide Al2O3, titanium oxide TiO2, silicon nitride Si3N4, silicon oxynitride SiON, and titanium nitride TiN; the material of the first low refractive layer includes silicon oxide SiO2.

11. The laminated structure according to claim 9 or 10, characterized in that: The thickness of the first high-refractive layer is in the range of 5-150 nm; the thickness of the first low-refractive layer is in the range of 10-200 nm.

12. The laminated structure according to any one of claims 9 to 11, characterized in that: The first low-refractive layer is doped with at least one of titanium Ti, zirconium Zr, copper Cu, and aluminum Al; the first high-refractive layer is doped with at least one of yttrium oxide Y2O3, aluminum oxide Al2O3, cerium oxide CeO2, calcium oxide CaO, and magnesium oxide MgO.

13. The laminated structure according to any one of claims 9 to 12, characterized in that: The stacked structure also includes: a second connecting layer, the first high-refractive layer is connected to the first low-refractive layer through the second connecting layer, the thickness of the second connecting layer ranges from 1 to 20 atomic layers, the second connecting layer is made of a bondable material, and the bondable material forms a chemical bond with the first high-refractive layer.

14. The laminated structure according to any one of claims 1 to 13, characterized in that: The anti-reflection layer includes N high-refractive layers and N low-reflective layers, and the N high-refractive layers and the N low-reflective layers are arranged at intervals, wherein N is an integer greater than or equal to 2.

15. An electronic device, characterized in that: It comprises a display module, and the laminated structure according to any one of claims 1 to 14, wherein the laminated structure is arranged on the light-emitting side of the display module.

16. A method for preparing a laminated structure, characterized in that: include: forming a hardened layer on the base film; Performing surface treatment on the side of the hardened layer away from the base film so that bonds are broken on the side of the hardened layer away from the base film; forming a first connection layer on the hardened layer, wherein the thickness of the first connection layer is in the range of 1-20 atomic layers, the first connection layer is made of a bondable material, the thickness of the first connection layer is in the range of 1-20 atomic layers, the first connection layer is made of a bondable material, and the bondable material forms a chemical bond with the broken bond of the hardened layer; forming an anti-reflection layer on the first connecting layer; An anti-fingerprint layer is formed on the anti-reflection layer.

17. The preparation method according to claim 16, characterized in that: The bondable material includes silicon atoms, the material of the hardened layer includes oxygen atoms, and the covalent bond formed between the hardened layer and the bondable material includes a silicon-oxygen covalent bond.

Citation Information

Patent Citations

  • Tactile feedback device

    CN115469747A

  • Anti-reflective film, method for manufacturing same,

    CN116953821A

  • Antireflection film, and electronic image display using the same

    JP2009003354A

  • Anti-reflective hardcoating film and manufacturing method of thereof

    KR1020130106670A

Cited By

  • Laminated structure, electronic device, and preparation method for laminated structure

    WO2026031766A1